PC magazine home networking solutions - Freed, Les (Wiley Pub., 2005)
Les Freed shares his many years of networking experience and insider status to guide readers step by step through the confusing and intimidating world of home networking . Features special emphasis on using the network for entertainment and digital media, offering invaluable how-to advice on sharing TV, video, photos, music, and more. Begins with the need-to-know basics of networking, including the various types of networking equipment and choosing the right type of network. Readers roll up their sleeves and actually construct their network-either wired or wireless-or by even using the existing electrical wiring already in the walls of their home. Shows readers how to set up all the necessary software on their Windows XP PC or Apple Mac OS X computer so they can quickly, easily, and safely share files, printers, and Internet connections